Development, Characterization, and Antimicrobial Activity of Gelatin/Chitosan/ZnO Nanoparticle Composite Films. Issue 7 (2nd October 2016) - Liu, Zunying; Lv, Meng; Li, Feng; Zeng, Mingyong
ABSTRACT: In order to enhance antimicrobial activity of the film, zinc oxide (ZnO) nanoparticles were incorporated in gelatin/chitosan composite film, and the physical-mechanical properties were investigated. The film-forming solution of gelatin/chitosan/ZnO films showed increased gel strength (GS), elastic modulus ( G' ), and viscous modulus ( G'' ) compared to that of the Control. Fish gelatin/chitosan/ZnO films showed lower water vapor permeability (WVP), higher glass transition temperatures ( T g ), and antibacterial activities against Staphylococcus aureus, Listeria monocytogenes, Escherichia coli, and Vibrio parahemolyticus . Fourier transform infrared spectra (FTIR) and microstructure studies indicated gelatin, chitosan, and ZnO interactions determined the properties of the composite film.